2009
DOI: 10.1128/jvi.01153-09
|View full text |Cite
|
Sign up to set email alerts
|

Defective Human Immunodeficiency Virus-Specific CD8 + T-Cell Polyfunctionality, Proliferation, and Cytotoxicity Are Not Restored by Antiretroviral Therapy

Abstract: Identifying the functions of human immunodeficiency virus (HIV)-specific CD8؉ T cells that are not merely modulated by the level of virus but clearly distinguish patients with immune control from those without such control is of paramount importance. Features of the HIV-specific CD8؉ T-cell response in antiretroviraltreated patients (designated Rx <50) and untreated patients (long-term nonprogressors [LTNP]) matched for very low HIV RNA levels were comprehensively examined. The proliferative capacity of HIV-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
179
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(197 citation statements)
references
References 53 publications
11
179
2
2
Order By: Relevance
“…As compared with acute infection such as influenza, HIV-specific CTL responses in infected patients are known to have significantly lower levels of polyfunctionality, and CTL dysfunction is not restored by antiretroviral therapy (9,35). Recent studies indicate that inhibition of the PD-1 pathway partially reverses low polyfunctionality associated with chronic viral infection (13).…”
Section: Upregulation Of Spry2 In High Antigen Concentration-induced mentioning
confidence: 99%
“…As compared with acute infection such as influenza, HIV-specific CTL responses in infected patients are known to have significantly lower levels of polyfunctionality, and CTL dysfunction is not restored by antiretroviral therapy (9,35). Recent studies indicate that inhibition of the PD-1 pathway partially reverses low polyfunctionality associated with chronic viral infection (13).…”
Section: Upregulation Of Spry2 In High Antigen Concentration-induced mentioning
confidence: 99%
“…HIV-1-specific T cells in the blood are functionally impaired during chronic HIV-1 infection (21)(22)(23)36), which is in part caused by exhaustion and overexpression of inhibitory receptors (11)(12)(13). These exhausted T cells lose effector functions and exhibit antigen-independent homeostatic proliferation (37).…”
mentioning
confidence: 99%
“…Many studies have shown that CD8 ϩ T cells from ESs are more effective at inhibiting viral replication in CD4 ϩ T cells than CD8 ϩ T cells from chronic progressors (CPs) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Furthermore, HIV-1-specific CD4 ϩ T cells from ESs have high-avidity T cell receptors and are more likely to maintain responses that are either proliferative, polyfunctional, or cytotoxic than effector CD4 ϩ T cells from CPs (12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%